2015
DOI: 10.1016/j.bbadis.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen induces the development of hernia in mice by activating MMP-2 and MMP-13 expression

Abstract: Hernia is a disease with defects in collagen synthesis/metabolism. However, the underlying mechanisms for hernia formation have not been fully defined. Tamoxifen is a selective estrogen receptor modulator and used for patients with breast cancer. Tamoxifen also has pleiotropic and side effects. Herein, we report that tamoxifen treatment resulted in an appearance of a large bulge in the low abdomen between the hind legs in male but not in female mice. The autopsy demonstrated that the low abdominal wall was bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…Total RNA was extracted from cells followed by cDNA synthesis as described (22). Real-time PCR was conducted using SYBR Green PCR Master Mix (Bio-Rad) and the following primers: CH25H forward, 5′-ATGTTGACCACGTGGAAGGT-3′ and CH25H reverse, 5′-TGGGAACTGTTTTCTTTGGG-3′; GAPDH forward, 5′-ACAACTTTGGCATTGTGAA-3′ and GAPDH reverse, 5′-GATGCAGGGATGATGTTCTG-3′.…”
Section: Cdna Synthesis and Quantitative Real-time Pcrmentioning
confidence: 99%
“…Total RNA was extracted from cells followed by cDNA synthesis as described (22). Real-time PCR was conducted using SYBR Green PCR Master Mix (Bio-Rad) and the following primers: CH25H forward, 5′-ATGTTGACCACGTGGAAGGT-3′ and CH25H reverse, 5′-TGGGAACTGTTTTCTTTGGG-3′; GAPDH forward, 5′-ACAACTTTGGCATTGTGAA-3′ and GAPDH reverse, 5′-GATGCAGGGATGATGTTCTG-3′.…”
Section: Cdna Synthesis and Quantitative Real-time Pcrmentioning
confidence: 99%
“…The potential side effects in men are infertility and gynecomastia (71). Ma et al reported that tamoxifen might cause hernia development in mice by activating matrix metalloproteinase expression (72). These interesting findings create an intersection for hernia and cancer and future studies could provide more surprising results on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…9). In some studies, the fibrotic modulation property of tamoxifen has been reported to act via the TGF-b [31][32][33][34] or ERK1/2 pathway [35,36]. However, the influence of tamoxifen on TGF-b signaling is still under debate, as opposing effects have been observed in different species and cell types [35,37].…”
Section: Discussionmentioning
confidence: 99%